A study on power output of horizontal-axis wind turbines under rain - Anh, Nguyen Tuan; Duc, Nguyen Huu (Vietnam Journal of Science and Technology, 2019)
The power of the wind turbine are significantly affected by the air conditions of the operating environment. Rain is a widespread phenomenon in many parts of the world especially in Vietnam, so exploring its effect on the power of wind turbines will provide valuable insights into the design of a new wind tower. In this paper, a method and a model is developed to estimate the effect of precipitation by simulating the actual physical processes of the rain drops forming on the surface of the blades of horizontal-axis wind turbines (HAWT), thereby determining optimal wetness, then power and performance respectively. Consequently, it makes a contribution to operation and control strategies for horizontal-axis wind turbines.